Petro Ivanovich Bilinsky - Ukrainian Association of Orthopedic Traumatologists, - (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is dedicated to the 60th anniversary of the birth of a doctor of medical sciences, a professor, a well-known orthopedist-traumatologist, a talented surgeon Bilinsky P.I.